Vermillion coated memorial stones - Banganga by Ghosh, Ayan (2023)
The north end of Banganga Tank has a collection of stone relics. They commonly depict a horse and rider, its features hidden under a thick layer of vermillion smeared by worshippers. What the stones represent or where they were sourced from remains unknown, though it is likely they are memorials erected for warriors who died in battle.